Sentimental memorials - Sodeman, Melissa (Stanford University Press, 2015)
'Sentimental Memorials' explores how popular women writers used the art form of the novel to record their changing relations to literary history. At the end of the eighteenth century, as sentimental fiction slipped out of emerging conceptions of literary value, Sophia Lee, Ann Radcliffe, Charlotte Smith, and Mary Robinson reflected on what changes in literature's meaning and status would mean for their own works and legacies. Their novels provide a means of understanding how women novelists clarified, protested, and finally memorialised the historical conditions under which they wrote.
10.11126/stanford/9780804791328.001.0001
Keywords: Smith; Charlotte Turner; Robinson; Mary; Lee; Sophia; Radcliffe; Anne Ward; Englisch; Roman; Frauenroman; Empfindsamkeit; English fiction; Women and literature; Sentimentalism in literature